2021
DOI: 10.1080/1828051x.2021.1978335
|View full text |Cite
|
Sign up to set email alerts
|

The use of dietary chromium associated with vitamins and minerals (synthetic and natural source) to improve some quality aspects of broiler thigh meat reared under heat stress condition

Abstract: The effect of chromium associated with vitamins and minerals (synthetic or natural ingredients) on broiler meat nutritional quality, subjected to heat stress conditions were evaluated. The 6week feeding trial was conducted on 120 unsexed 1-day-old Cobb 500 broilers, assigned to 4 treatments and housed in digestibility cages at 32 C constant temperature. Compared to the control diet (C), the experimental diets were supplemented with 200 mg/kg diet chromium picolinate (Cr), as follows: Cr-AA has 0.25 g ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In the current study, the ADFI and ADG significantly increased in the 0.4 mg/kg supplemented group compared with the HT group, indicating that dietary supplementation with 0.4 mg/kg Cr as Cr-Pic can reduced the severity of impaired performance under heat stress. This corresponds with previous results indicating that Cr-Pic has a positive effect on growth performance in broilers under heat stress [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the ADFI and ADG significantly increased in the 0.4 mg/kg supplemented group compared with the HT group, indicating that dietary supplementation with 0.4 mg/kg Cr as Cr-Pic can reduced the severity of impaired performance under heat stress. This corresponds with previous results indicating that Cr-Pic has a positive effect on growth performance in broilers under heat stress [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…A similar trend was observed by [ 29 ] when feeding minerals and medicinal plant extracts. Others [ 69 ] also showed a positive effect of Cr on Fe and Zn deposition. Feeding Cr alone increased Mn level but decreased Zn content in thigh meat compared to basal treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The literature is controversial regarding the interaction between Cr and Fe. Some authors have shown that Cr and Fe are antagonistic minerals, and Cr supplementation affects Fe absorption (Pechova and Pavlata, 2007) while others have shown that Cr supplementation increases Fe and Zn levels in chicken meat (Untea et al, 2021). However, the Fe levels were significantly lower in the liver from Cr-CWS group compared to the other groups.…”
Section: Resultsmentioning
confidence: 97%
“…Contrary to our findings on liver crude fat, other authors have shown different results on deposit tissues (breast and thigh). For example, some authors showed that Cr-Zn and Cr-VC supplementation to the diet of heat stressed broiler decreased the content of crude fat in breast (Untea et al, 2021) and thigh meat (Saracila et al, 2021a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation